HUBUNGAN ETNIS JAWA DAN TIONGHOA DALAM NOVEL TUNGGAK-TUNGGAK JATI - Sungkowati, Yulitin (Diksi, 2015)
This article tries to explore the relationship between Javanese and Chinese ethnic groups in Tunggak-Tunggak Jati, a Javanese novel by Esmiet. The novel describes the older Javanese generation' views of the Chinese ethnic group and vice versa based on prejudice and stereotype. But the younger Javanese and Chinese generations try to eradicate the prejudice and ethnic partition. The young Chinese generation's consciousness that Indonesia is their country results in the feeling that they are not different from the Javanese ethnic group and they are not strangers in Indonesia. The young Javanese generation also tries to accept the Chinese ethnic group as part of Indonesia. This novel also shows that the Javanese and Chinese ethnic groups need each other in social interaction to establish true relationship and to respect each other through, for example, marriage. Keywords: relationship, ethnic group, Javanese, Chinese